Eco-efficiency assessment of conventional OPC/PPC replacement by LC3 in Cuban residential buildings. (August 2019) - Cancio Díaz, Y; Sánchez Berriel, S; Sánchez Machado, I R; Martirena Hernández, J F; Habert, G
Abstract: This paper aims at assessing the sustainability of replacing conventional OPC/PPC by Limestone Calcined Clay Cement (LC3) in Cuba. Authors conducted an eco-efficiency (E-E) analysis supported by E-E ratios, which in turn are rooted on the environmental assessment (Life Cycle Assessment, LCA) and the economic analysis (Economic Value Added, EVA). Taking case studies in Villa Clara province capital district, three construction methods were compared and further conclusions emerged with regard to economic and ecological criteria. A square meter of built area was employed as functional unit. According to main results, Grand panel technique appears to be the benchmarking method, followed by Forsa system and, finally, concrete block technique. LC3 blend outperforms OPC/PPC from both economic and environmental perspective. Furthermore, productive efficiency potentials were found on the field of material selection and raw material procurement. Authors provided decision-makers with some policy recommendations in order to contribute enhancing the sustainable use of LC3 in Cuban construction sector.